Distribution characteristics and morphological comparison of telocytes in the aortic bulb and myocardium of yak heart - Jinhan Lv; Ligang Yuan; Guojuan Chen; Long Ma; Yumei Qi; Jianlin Zeng; Xiaofen Wang; Yajuan Jin (BMC Veterinary Research)
Abstract Background Telocytes (TCs) are small interstitial cells that extend into multiple bead-like protrusions called telopodes (TPs). TCs are widely found in many tissues and organs, form connections with almost all types of cardiomyocytes, and participate in regulating cardiac microenvironment homeostasis. Methods In this study, transmission electron microscopy combined with special staining techniques (Gomori’s, Masson’s trichrome, and toluidine blue staining) were used to analyse the ultrastructure, distribution, and cytochemical characteristics of TCs in yak hearts. Immunohistochemistry and immunofluorescence double staining techniques were combined to identify the immunophenotypic characteristics of TCs functional markers (CD34, CD117, PDGFR-α and α-SMA) and further reveal their potential functions. Results The results showed that the TCs in the aortic bulb of yak hearts had prominent nuclei, and thin, long TPs with abundant secretory vesicles. TCs in the myocardial tissue exhibited irregularly shaped nuclei, shorter TPs, and connections with myocardial fibres and adjacent capillaries, forming a complex TC network. Immunohistochemical results demonstrated the positive expression of functional markers CD34, CD117, α-SMA and PDGFR-α in both the aortic bulb and myocardium. Immunofluorescence double staining results indicated co-expression of CD34/CD117, CD34/α-SMA, and CD117/PDGFR-α in TCs. Conclusion This is the first study to report the presence of TCs in the aortic bulb and myocardium of yak hearts and that it may form TC networks that mainly participate in mechanical support and cell communication in the heart. The presence and distribution characteristics of TCs in the heart of yaks provide important clues for further research on the role of TC networks in the adaptability of plateau animals to the environment.